Identification of CD8+ T cell subsets that normalize in early-treated people living with HIV receiving antiretroviral therapy (2022)
ABSTRACT:Background: Although combined antiretroviral therapy (cART) has decreased the mortality associated with HIV infection, complete immune reconstitution is not achieved despite viral suppression. Alterations of CD8+ T cells and some of their subpopulations, such as interleukin (IL)-17-producing cells, are evidenced in treated individuals and are associated with systemic infammation and adverse disease outcomes. We sought to evaluate if diferent CD8+ T cell subsets are diferentially normalized during a clinical follow-up of people living with HIV (PLWH) receiving suppressive cART. Methods: We explored the changes in the frequencies, activation/exhaustion phenotypes (HLA-DR, CD38, PD-1, and TIM-3), and function (total and HIV-specifc cells expressing CD107a, perforin, granzyme B, interferon [IFN]-γ and IL-17) of CD8+ T cells from early-treated PLWH receiving cART in a 1-year follow-up, using a multidimensional fow cytom‑ etry approach. Results: Despite continuous cART-induced viral suppression and recovery of CD4+ T cells, after a 1-year follow-up, the CD8+ T cell counts, CD4:CD8 ratio, PD-1 expression, and IL-17 production by CD8+ T cells exhibited incomplete normalization compared with seronegative controls. However, the proportion of CD8+ T cells with an exhausted phenotype (co-expressing PD-1 andTIM-3), and cells co-expressing cytotoxic molecules (Perforin and Granzyme B), reached normalization. Conclusions: Although suppressive cART achieves normalization of CD4+ T cell counts, only particular subsets of CD8+ T cells are more rapidly normalized in PLWH receiving cART, which could be routinely used as biomarkers for therapy efciency in these patients